Análise da qualidade de vida no trabalho em uma instituição pública de ensino no município de Abaetetuba-PA - BALHEIRO, Deidiane Rodrigues (2019)
The objective of this study was to carry out a study on Quality of Life at Work (QWL) at a state school in the city of Abaetetuba / PA, using basic concepts and practices of quality management, strengthening of physical, psychological, personal and professional. is relevant to achieving a good quality of life in the workplace. To do this, we applied a checklist with a target audience of twenty-five employees of the institution, teachers, pedagogical coordinators, administrative assistants, servers and vigilantes, both of the effective staff, and contractors, in order to verify that the indicators most influence Quality of Life at Work. Analysis of statistical data through Microsoft Excel software, illustrating presentation data in graphs and graphs exposing people's satisfaction levels in relation to imposed QWL. A brainstorming session, a list of diagnoses as causes of employee dissatisfaction problems, and a plan of action with the use of the 5W1H quality tool were carried out. in order to obtain the diagnosis of the consultation, the study demonstrated a range of information that would serve as a basis for discussions and discussions on future work and inclusion activities in all areas. the functional framework of the school.